The importance of continuing education of teachers who accompany students with disabilities in the regular school (Research, Society and Development, 2019)
The aim of this article is to present the results of a study in which there is a continuous study of the teachers that accompany students with disabilities in the regular school of education and their contribution to their practical action in the classroom. The study sample consisted of 14 elementary school teachers from the municipal public network of the city of Alegrete / RS. Data collection was carried out in 2017. In the data collection, questionnaires, reflexive conversational wheels and mini-courses were carried out with specialized professionals, who approached the historical and legal aspects and the importance of adapting the curriculum to the achievement of school inclusion. The analysis of the study points out that there is fragility in training for the efficient exercise of teaching practice with school inclusion, emphasizing the contributions of continuing education with an approach focused on curriculum adaptations, knowledge of the history and legal issues of the inclusive process of students with disabilities in the regular school of education.